The fever tree - McVeigh, Jennifer (G. P. Putnam's Sons, 2013)
South Africa, 1880. Frances Irvine, destitute in the wake of her father's sudden death, is forced to abandon her life of wealth and privilege in London and emigrate to the Cape. In this remote and inhospitable land she becomes entangled with two very different men, leading her into the dark heart of the diamond mines. Torn between passion and integrity, she makes a choice that has devastating consequences.